Delayed Time to Peak Velocity Is Useful for Detecting Severe Aortic Stenosis. Issue 10 (October 2016) - Kamimura, Daisuke; Hans, Sartaj; Suzuki, Takeki; Fox, Ervin R.; Hall, Michael E.; Musani, Solomon K.; McMullan, Michael R.; Little, William C.
Abstract : Background: Time to peak velocity (TPV) is an echocardiographic variable that can be easily measured and reflects a late peaking murmur, a classic physical finding suggesting severe aortic stenosis (AS). The aim of this study was to investigate the usefulness of TPV to evaluate AS severity. Methods and Results: This study included 700 AS patients, whose aortic valve area (AVA) was <1.5 cm 2, and 200 control patients. The TPV was defined as the time from aortic valve opening to when the flow velocity across the aortic valve reaches its peak. AS severity was classified as follows: High gradient severe AS, mean pressure gradient ≥40 mm Hg and AVA index (AVAI) <0.6 cm 2 /m 2 ; Low gradient severe AS, mean pressure gradient <40 mm Hg, AVAI <0.6 cm 2 /m 2, and dimensionless index <0.25; moderate AS, mean pressure gradient <40 mm Hg, AVAI ≥0.6 cm 2 /m 2 . The area under the receiver operating characteristic curve of TPV to predict high gradient severe AS was 0.94 (95% CI: 0.92–0.97, P <0.001). TPV was significantly delayed in low gradient severe AS compared with moderate AS both in patients with preserved (102±13 ms versus 83±13 ms, P <0.001) and with reduced ejection fraction (110±18 ms versus 88±13 ms, P <0.001). Delayed TPV was associated with increased all‐cause mortality or need for aortic valve replacement after adjustment for confounders (hazard ratio for first quartile, reference is fourth quartile: 7.31, 95% CI 4.26–12.53, P <0.001). Conclusions: TPV is useful to evaluate AS severity and predict poor prognosis of AS patients.